Active behaviors and screen time in offspring of parents with major depressive disorder, bipolar disorder and schizophrenia. (March 2020) - Pizzo, Alex; Drobinin, Vlad; Sandstrom, Andrea; Zwicker, Alyson; Howes Vallis, Emily; Fine, Alexa; Rempel, Sheri; Stephens, Meg; Howard, Cynthia; Villars, Kelsey; MacKenzie, Lynn E.; Propper, Lukas; et al.
Highlights: Offspring of parents with mood disorder spend less time in active behaviors. Offspring of parents with mood disorders spend more time using screens. Mothers' current depressive symptoms are associated with less offspring active time. Mothers' current depressive symptoms are associated with more offspring screen time. Parental schizophrenia has no significant effect on offspring screen and active time. Abstract: Activities may be modifiable factors that moderate the risk and resilience in the development of mental health and illness. Youth who spend more time using screens are more likely to have poor mental health. Conversely, time spent engaged in active behaviors (i.e., physical activity, socializing and reading) is associated with better mental health. The choice of activities may be important in offspring of parents with mental illness, who are at increased risk for developing mental disorders. Among 357 youth of the FORBOW (Families Overcoming Risks and Building Opportunities for Well-being) cohort aged 6–21, we examined whether parental diagnosis of mental illness (i.e., major depressive disorder, schizophrenia and bipolar disorder) and current levels of depression influenced the amount of time their offspring spent using screens and engaging in active behaviors. Parental history of mental illness and higher levels of current depression in mothers were associated with less time spent engaged in active behaviors and more time spent using screens. Creating opportunities and incentives for active behaviors may redress the balance between youth with and without a familial history of mental illness.